In Vitro Activity, Stability and Molecular Characterization of Eight Potent Bacteriophages Infecting Carbapenem-resistant Klebsiella Pneumoniae - Abeer Ameen Baqer; Kokxin Fang; Norfarhan Mohd-Assaad; Norefrina Shafinaz Md Nor; Siti Noor Adnalizawati Adnan (MDPI, 2024)
Indexed by SCOPUS/ERA